2021
DOI: 10.1155/2021/5577740
|View full text |Cite
|
Sign up to set email alerts
|

Brittleness Index of High-Rank Coal Reservoir and Its Influencing Factors in Mabidong Block, Qinshui Basin, China

Abstract: Brittleness index is an important mechanical index to evaluate the fracturability of conventional oil and gas reservoirs. However, the brittleness index of an organic coal reservoir is more complex. In this study, based on array sonic logging and density logging data, coal brittleness index is calculated using an elastic parameter method in the Mabidong coalbed methane (CBM) block in southern Qinshui Basin. In combination with coal-body structure observation, the maceral analysis, and proximate data of coal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Hou et al (2020) measured the hardness and elastic modulus of vitrinite, inertinite and liptinite by depth-sensing nanoindentation, and the hardness values of the three maceral groups were 0.52GPa~0.78 GPa, 0.78 GPa ~1.37 GPa and 0.18 GPa ~0.52 GPa, respectively; the elastic modulus of the three maceral groups was 5.46 GPa ~6.97 GPa, 7.19 GPa ~8.91 GPa and 2.60 GPa ~4.42 GPa. Zhang (2021b) found that the maceral group content also affects the Young's modulus and Poisson's ratio of coal. They calculated the brittleness index of coal by equations 1-3.…”
Section: Structure Differences Utilization In Coal Beneficiationmentioning
confidence: 99%
“…Hou et al (2020) measured the hardness and elastic modulus of vitrinite, inertinite and liptinite by depth-sensing nanoindentation, and the hardness values of the three maceral groups were 0.52GPa~0.78 GPa, 0.78 GPa ~1.37 GPa and 0.18 GPa ~0.52 GPa, respectively; the elastic modulus of the three maceral groups was 5.46 GPa ~6.97 GPa, 7.19 GPa ~8.91 GPa and 2.60 GPa ~4.42 GPa. Zhang (2021b) found that the maceral group content also affects the Young's modulus and Poisson's ratio of coal. They calculated the brittleness index of coal by equations 1-3.…”
Section: Structure Differences Utilization In Coal Beneficiationmentioning
confidence: 99%
“…Therefore, it is urgent to establish an effective method for distinguishing coal texture. Logging curves, as an indirect parameter for identifying coal texture, have applicability advantages compared to identifying coal texture with coal cores, which may be affected by drilling and lead to misjudgment . Early research on coal texture prediction based on logging curves primarily employed cluster analysis and the Protodyakonov’s coefficient method .…”
Section: Introductionmentioning
confidence: 99%
“…Logging curves, as an indirect parameter for identifying coal texture, have applicability advantages compared to identifying coal texture with coal cores, which may be affected by drilling and lead to misjudgment. 4 Early research on coal texture prediction based on logging curves primarily employed cluster analysis 5 and the Protodyakonov’s coefficient method. 6 Subsequently, methods such as Archie’s formula, 7 coal texture index, 8 brittleness index, 9 geological strength index (GSI), 10 K-means algorithm, 11 principal component analysis, 12 neural network, 13 , 14 Fisher discriminant analysis, 15 and other quantitative classification techniques were gradually introduced.…”
Section: Introductionmentioning
confidence: 99%